2019
DOI: 10.3991/ijim.v13i09.9566
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smartphone Addiction, Achievement Motivation, and Textbook Reading Intensity on Students’ Academic Achievement

Abstract: <h1>This study investigates the effect of smartphone addiction, achievement motivation, and textbook reading intensity on academic achievement. This quantitative study involved 720 students from two public universities. The cluster random sampling technique and three psychological scales namely Smartphone Addiction Scale, Achievement Motivation Scale, and Reading Textbook Intensity Scale were employed for data collection. The data were analyzed using path analysis technique. The study found that (i) smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
(21 reference statements)
0
20
0
6
Order By: Relevance
“…In addition, contextual experience can also be done with a virtual reality laboratory (VR) by manipulating objects in virtual scenes that resemble the real world [19]. Virtual reality (VR) laboratory implementation can be done using a tablet, PC or smartphone that can be accessed anytime and anywhere [20].Contextual experience obtained by using cellular features, which was following the learning environment, so the integration of pedagogical and technology elements became complex [21], and the use of multimedia contributed to the level of understanding of the material [22]. The task of the teacher in this case needs to be reminded the use of digital technology needs to be balanced with humanistic literacy so as not to violate digital ethics [23].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, contextual experience can also be done with a virtual reality laboratory (VR) by manipulating objects in virtual scenes that resemble the real world [19]. Virtual reality (VR) laboratory implementation can be done using a tablet, PC or smartphone that can be accessed anytime and anywhere [20].Contextual experience obtained by using cellular features, which was following the learning environment, so the integration of pedagogical and technology elements became complex [21], and the use of multimedia contributed to the level of understanding of the material [22]. The task of the teacher in this case needs to be reminded the use of digital technology needs to be balanced with humanistic literacy so as not to violate digital ethics [23].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study indicate that detoxification is a fairly good method for treating sleep disorders. Smartphone addiction and achievement motivation directly affect the intensity of reading academic textbooks, and smartphones addiction, achievement motivation, and the intensity of reading academic textbooks directly affect the academic achievement [13].…”
Section: Methodsmentioning
confidence: 99%
“…The same thing was also revealed that the effect of smartphone addiction affected achievement motivation, and the intensity of reading text books on academic achievements. [4] Based on the survey results, adolescents show prevalence and incidence rates on specific problems related to biopsychosocial health, which in this case relates to anxiety when away from gadgets. In connection with the phenomenon of smartphone addiction, it also happens a lot in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from self-efficacy, achievement motivation is vital for everyone [16], especially those who have a dual role, namely playing as a student and a student. Achievement motivation is a crucial characteristic of behavior that impacts individuals in dealing with their tasks [17].…”
Section: Introductionmentioning
confidence: 99%